Development of Tourism Villages Based on Local Wisdom and Technology In Lantan Village, North Batukliang - Wibisana, Bayu; Pratama, Yusuf Hendra; Firmansyah, Firmansyah; Darayani, Dhiafah Hera; Sahwan, Sahwan; Piya, Mina Ukup (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Lantan Village Area, North Baukliang District, Central Lombok Regency has very potential for rural tourism to be developed. The village has interesting natural characteristics and unique social and cultural life. This potential must be encouraged and developed following the socio-cultural characteristics of the community. One of the problems that exist in the Lantan Village Tourism area, North Batukliang District, Central Lombok Region is the lack of marketing of SME products and tourist sites, even though SME products and tourist areas are good. Because it is considered less than optimal, the use of technology can facilitate the dissemination of information on SME products and tourist areas. For example, the use of travel guide apps that provide historical information, local stories, and activity recommendations can provide an in-depth interaction between tourists and local culture. The purpose of this socialization is; 1) Increase marketing of SME products and tourist sites based on social media and websites to be more widely known; 2) Encourage and motivate the community to be enthusiastic in learning and always maintain the preservation of tourism in Lantan Village. The results of this community service were followed by very high community enthusiasm. In addition, the community also gains knowledge related to technology which can be an effective means of spurring tourism progress through online promotion, as well as the use of the internet which is an inseparable component of technology.